Agroforestry prototypes for Belize - Ibrahim, Muhammad Akbar (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), 2014)
The contents of this document are aimed at local technicians, scientific staff and students of the agricultural college of the University in Belize. It is hoped that they will provide an insight into the concepts that are the basis for ecologically sustainable and economically competitive agroforestry technologies as well as the practical considerations involved in their establishment and management. It is recommended that the information and methods presented be used as a prescription or blueprint because of the many different situations which users of these course notes will face. It is essential that each agroforestry technology is adapted to the particular biophysical and socio-economic characteristics of each site. It is up to the individuals using these course notes to apply them to their own particular situations. We hope that this document will assist national agricultural and forestry staff to develop and establish successful agroforestry systems in Belize.